Legal Protection for Tik Tok Shop Buyers: Comparison between China and Indonesia - Pratama, Naufal Bagus; Deniesa, Salsabilla (Universitas Muhammadiyah Yogyakarta, 2023)
The nature and scale of e-commerce are constantly changing. In today's world, the concept of internet purchasing became ubiquitous. All the purchases that consumers make is safeguarded by a set of policies in the form of rules imposed in each country; thus, the evolution of consumer protection is also inextricable from global influences. The term consumer protection refers to an umbrella term that encompasses many different aspects of economic transactions. The relevance of the law rests in the fact that the regulation works to protect individuals and the rights they are entitled to. In spite of the significance they have, customers frequently find themselves victimized by unethical commercial activities. This article describes the proliferation of E-commerce and the legal protection of the e-consumers who conduct buying and selling transactions, particularly in the TikTok Shop platform. This normative legal research relies on secondary data and employs both statutory and comparative approach. The finding shows that China has established a new law to safeguard and maximize a healthy shopping environment on an e-commerce platform. On the other side, Indonesia has not had a specific regulation for e-commerce yet, accordingly the legal protection for Tik Tok Shop buyers relies to the existing law, namely the Law No. 8 of 1999 concerning consumer protection.The nature and scale of e-commerce are constantly changing. In today's world, the concept of internet purchasing became ubiquitous. All the purchases that consumers make is safeguarded by a set of policies in the form of rules imposed in each country; thus, the evolution of consumer protection is also inextricable from global influences. The term consumer protection refers to an umbrella term that encompasses many different aspects of economic transactions. The relevance of the law rests in the fact that the regulation works to protect individuals and the rights they are entitled to. In spite of the significance they have, customers frequently find themselves victimized by unethical commercial activities. This article describes the proliferation of E-commerce and the legal protection of the e-consumers who conduct buying and selling transactions, particularly in the TikTok Shop platform. This normative legal research relies on secondary data and employs both statutory and comparative approach. The finding shows that China has established a new law to safeguard and maximize a healthy shopping environment on an e-commerce platform. On the other side, Indonesia has not had a specific regulation for e-commerce yet, accordingly the legal protection for Tik Tok Shop buyers relies to the existing law, namely the Law No. 8 of 1999 concerning consumer protection.